Effect of Bamboo Flour Content on the Properties of PLA-based and PBAT-Based Wood-Plastic Composites - Liu Ling; Chen Chen; He Huihui; Li Jun; Su Yu; Jiang Haojun; Lei Zhendong (E3S Web of Conferences, 2025)
In this study, different mass fraction (0%, 10%, 20%, 30%) of bamboo flour (BF) was blended with PLA pellets and PBAT masterbatch via extrusion compounding process. The effect of bamboo flour content on the thermal and mechanical properties of the prepared wood-plastic composites (WPCs) arecharacterized by SEM, XRD, and DSC. The results show that the addition of BF did not alter the crystal structure of PLA and PBAT. However, as the bamboo flour content increase to 20% and 30%, agglomeration and uneven distribution are observed for the composites. Additionally, the initial decomposition temperature decreases, and the tensile strength declines.